Respuesta :

Answer:

p + 9q.

Step-by-step explanation:

The explicit formula for the nth term of an A. P is

an = a1 + d(n - 1) where a1 = the first term and d = the common difference.

So the 10th term when a1 = p and d = q is:

a10 =  p + q(10 - 1)

= p + 9q.

Good morning,

__________________

Answer:

the Tenth term = p+9q.

__________________

Step-by-step explanation:

let U₁ be The first term, then U₁=q and U₁₀ be The 10th term

U₁₀=p+(10-1)×U₁

Then,

U₁₀=p+9q.

______________________________________________

:)

ACCESS MORE